Application of acoustic methods to assessment of concrete humidity influence on the process of concrete destruction - J. PYSZNIAK; J. HOŁA (Archives of Acoustics)
Owing to application of acoustic research methods, i.e. the ultrasound and the acoustic emission methods, it was pointed out in the paper that concrete humidity is of an essential influence on the process of concrete destruction. It was also proved that the totting sum of the acoustic emission recorded during the process of destruction of concrete is clearly determined by bulk humidity of the material under investigation. The examination results submitted here refer to plain concrete subjected to an influence of innediate loads during tests of compressing it quasi-axially and stretching according to Brazilian method.